A Green Strategy to Enhance a Liquid–Liquid Heterogeneous Reaction with a Magnetic Recyclable Pickering Emulsion. Issue 4 (23rd January 2015) - Feng, Linbin; Wang, Jianli; Chen, Liang; Lu, Meizhen; Zheng, Zhi; Jing, Ren; Chen, Hualiang; Shen, Xianbo
Abstract This work described a general strategy to enhance a typical organic–aqueous heterogeneous green oxidation reaction by introducing surface tunable magnetic nanoparticles into liquids to form a controllable Pickering emulsion. We synthesized cross‐linked polystyrene (PS)‐covered Fe3O4 nanoparticles grafted with different N‐alkyl imidazoles and systematically discussed the effect of surface properties on the formation of emulsions. By loading such particles, the dichloromethane–water‐based 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl‐mediated Montanari oxidation system was converted from the unstable millimeter‐scale dispersion into a stable micrometer‐scale emulsion, which significantly reduced the reactant transfer distance and resulted in a significantly high overall reaction rate. This reaction efficiency is elucidated in terms of unique properties inherent in an emulsion, including the self‐assembly of Fe3O4/PS and Fe3O4/PS[im‐Cn]Cl (n=1, 4, 6, and 10) nanoparticles, well ensuring a large specific surface area of the water–oil interface.